2014
DOI: 10.2478/s11534-014-0480-9
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type-II universe with linear equation of state

Abstract: Abstract:We have studied anisotropic and homogeneous Bianchi type-II cosmological model with linear equation of state (EoS) = αρ − β, where α and β are constants, in General Relativity. In order to obtain the solutions of the field equations we have assumed the geometrical restriction that expansion scalar θ is proportional to shear scalar σ . The geometrical and physical aspects of the model are also studied.PACS (2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It is observed that, the fluid work as dark energy (negative pressure p ) depending on the particular values of α and β was shown in Figure 2 [12,14].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is observed that, the fluid work as dark energy (negative pressure p ) depending on the particular values of α and β was shown in Figure 2 [12,14].…”
Section: Resultsmentioning
confidence: 96%
“…In this way, all possible expansion histories, the power law expansion, (12), and the exponential expansion, (13), have been covered.…”
Section: In View Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…S.D deo et al studied Bianchi type -III Cosmological model filled with a Magnetized Cosmic Strings is investigated in general relativity [8] . KS Adhav et al studied on Bianchi type-III cosmological model in General Relativity with linear equation of state (EoS) i.e 𝑝 = 𝛼𝜌 − 𝛽, where 𝛼 and 𝛽 are constants [9] . Priyanka Kumari et al studied on anisotropic Bianchi type-III cosmological model in the presence of a bulk viscous fluid within the framework of Lyra geometry with time-dependent displacement vector [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Many authors viz. Abbott and Wise 1 , Adhav et al 2 , Albrecht and Steinhardt 3 , Bali et al 8,9,10 , Reddy et al 17,18 , Katore et al 14 , Jat et al 12,13 studied inflationary cosmological models in different Bianchi space-times with self interacting scalar field in General Relativity.…”
Section: Introductionmentioning
confidence: 99%